Penggunaan Media Pembelajaran Komik Untuk Meningkatkan Kemampuan Menulis Cerpen di Era Metaverse - Falah, Nurul; Dalman, Dalman; Salamah, Salamah (Universitas Negeri Padang, 2025)
Students' short story writing skills in the digital age face challenges in the form of low interest, limited imagination, and the dominance of interactive visual media. The development of metaverse technology presents new opportunities to deliver more innovative and contextual learning media. This study aims to explore the effectiveness of using comic learning media in improving students' short story writing skills in the metaverse era. The research was conducted at MAN 1 Lampung Tengah with 36 students from class XII IPA 6 as subjects. The method used was classroom action research (CAR) consisting of two cycles. The data analysis technique was carried out in several stages, namely data reduction, data presentation, and conclusion drawing. The results of the study showed an increase in students' short story writing skills, with students' assessments of content appropriateness and linguistic aspects. The average short story writing score increased after using comic media, with the largest increase being 40%. Comic media has been proven to stimulate students' imagination, facilitate understanding of the storyline, and increase active involvement in the learning process. Thus, the use of comic learning media in the metaverse era can be an innovative alternative to improve short story writing skills while fostering students' interest in literacy.